Detrimental Effects of Slate Pencil : A Review - Rutuja T. Hagare; Manjushri S. Bagul (International Journal of Scientific Research in Science and Technology, 2024)
Slate pencil dust, often used in various cultures for its sensory properties, presents a concerning health hazard when inhaled or ingested. The possible harmful effects of slate pencil dust on human health are summed up in this article. The dust’s tiny particles, which are mostly made of minerals like kaolinite and talc, can cause gastrointestinal disorders, respiratory ailments, and dangers to one’s general health. The sources of exposure, the physiological effect of slate pencil dust, and the significance of increasing public awareness are all covered in this review. The result emphasize how important it is to promote safe alternatives and implement preventive measures in order to reduce the health risk related to exposure to slate pencil dust.
Keywords: Slate Pencil; Dust; Industries; Silicosis; Breathing; Pneumoconiosis